A Systematic Literature Review of Internal Quality Assurance in Early Childhood Education in Developed and Developing Countries - Yuli Pujianti; Siti Aminah; Entin Nuryati; Agus Mulyanto; Aimi Farina Sariff (Indonesian Journal of Educational Research and Review)
Internal Quality Assurance (IQA) is a critical component in early childhood education (ECE) to ensure that learning services meet established standards and deliver high-quality educational experiences for young children. This study aims to analyze the approaches, implementation practices, and challenges of IQA in ECE institutions through a Systematic Literature Review (SLR). The data were obtained from peer-reviewed articles published between 2014 and 2024 indexed in the Scopus database. Thematic analysis was employed to identify recurring patterns and key themes related to three dimensions of quality: structural, process, and outcome. The findings reveal that countries with more established education systems tend to integrate continuous evaluation and professional development systematically, whereas nations with limited capacity face significant challenges in terms of funding, training, and infrastructure. The study concludes that effective IQA requires a contextualized and collaborative approach, supported by consistent policy frameworks to enhance the global quality of ECE. These insights contribute conceptually to the development of adaptive and responsive quality assurance systems across diverse educational settings.